Design of an Efficient Full Adder Based on 5- Input Majority Gate In Coplanar Quantum Dot Cellular Automata - A.Chandrasekaran; K.Senthil Kumar (Journal of Power Electronics and Devices, 2017)
In combinational digital circuits, design of half adder, half subtractor, full adder and full subtractor is a promising one. In this paper, an improved full adder circuit is proposed using Quantum dot Cellular Automata (QCA) technology. When compared to other full adder circuits, the proposed design has less number of cells as well as area and delay is at minimum value. To design this full adder, a different approach for sum and carry outputs of full adder has been used. The simulation result obtained from the QCADesigner software confirms that the presented circuits functioning well and can be used as potential candidate in the design of combinational circuits in QCA technology. Finally the proposed QCA full adder is designed by using 5 input majority gate and acceptable results are achieved.